Adult intestinal malrotation: a case report - Pradiptha, Nyoman T.; Wiargitha, Ketut (International Journal of Research in Medical Sciences, 2019)
Midgut malrotation is an incomplete rotation of the intestine which occurs during foetal development and usually presents in the neonatal period. The bowel is not fixed adequately and is thus held by a precariously narrow-based mesentery. The incidence of malrotation has been estimated at 1 in 6000 live births, it is rare for malrotation to present in adulthood. Author report a 40-year-old man presented to emergency department with generalized abdominal pain. His symptoms began 2 days before admission. The patient really weak and his mental state was somnolence. His abdomen was slightly extended, and intestinal peristalsis was obscure. Abdominal X-rays revealed dilatation of gastric, coiled spring appearance without free air and step ladder pattern. The patient then underwent laparotomy exploration. Upon entering the abdomen, ileum was noted to completely mobilized and founded volvulus segment, a clockwise twisting three times, about 30 cm proximal from ICJ, and soon author released it. The ligament of Treitz misplaced, there was in the right lower quadrant, close by ICJ. Then about 110 cm segment of ileum necrotic, the rest of the small bowel was normal, author found internal hernia in the right lower quadrant and there was Ladd's band. Clinicians should be aware of this serious cause of abdominal pain. The diagnosis of malrotation in adulthood is often delayed. Complete resolution of acute obstruction or chronic abdominal pain is the result of a high index of suspicion for malrotation, appropriate diagnostic studies, and aggressive treatment.